The S···P noncovalent interaction: diverse chalcogen bonds. (4th May 2017) - Zabardasti, Abedien; Afrouzi, Hossein; Kakanejadifard, Ali; Jamshidi, Zahra
ABSTRACT: The S···P interactions in the complexes of HSX (X = F, Cl, Br, I) with PH n Me3- n ( n  = 0–3) have been investigated with ab initio calculations at the MP2/aug-cc-pVDZ and MP2/aug-cc-pVTZ//MP2/aug-cc-pVDZ level of theory. The interaction energies and structural properties of intermolecular complexes have been analyzed. Results of QTAIM analysis are dealing with expand of interactions, including pure closed-shell interactions (van der Waals interactions and chalcogen bonding, YB), partially covalent closed-shell (CS; Charge Transfer) and shared-shell interactions (SS; weak covalent bond and very strong YB) for these complexes. The energy decomposition analysis (EDA) showed that electrostatic interactions are an important contributing factor for these complexes. In considering second-order contributions, the donor-acceptor pair charge transfer (CT) is most important. These findings are consistent with the Electron Localization Function (ELF) isosurface of the complexes. In each series of HXS:PH n Me3- n -chalcogen bond complexes with increasing basicity of phosphines, the stability and S···P bond strength of adducts were increased so that the HXS:PMe3 (X = F, Cl, Br) complexes had very strong S···P chalcogen interactions with nearly covalent characters. GRAPHICAL ABSTRACT: